PENGARUH EKSISTENSI PERUSAHAAN, PROFITABILITAS, LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM BURSA EFEK INDONESIA TAHUN 2017-2020 - Diyan Ratna Widiyanti; Junaidi Junaidi; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
The manufacturing industry is the leading industry and can be said to be the largest at the ASEAN level with a percentage of 20.27 percent at the national level. The purpose of this study is to clarify the impact of a company's existence, profitability and liquidity on the dividend policy of manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020. The method used is a quantitative method that samples 30 companies listed on the Indonesia Stock Exchange. As a result of this survey, the existence of the company does not have a significant influence on the dividend payment ratio (dividend policy). The liquidity of a company has a great influence on the dividend payment ratio (dividend policy). The profitability of a company has a great influence on the dividend payment ratio (dividend policy). This study has been tested and carried out in accordance with scientific practice, but it still has limitations, namely this research only uses a period of 3 years from 2017 - 2020. The research topic focuses only on manufacturing companies listed on the Indonesian Stock Exchange where there are 193 listed companies. However, the researchers only used 30 companies. Meanwhile, suggestions that can be given to further researchers are that further researchers can increase their observation period and are expected to add independent variables. In addition, the advice that can be given to company owners is that management is expected to pay more attention to dividend payments to shareholders. Investors who want to invest are advised to analyze the performance of the company and pay more attention to the performance of the company so that they are not affected by the false increase in profitsKeyword : Company Existence, Profitability, Liquidity On Dividend Policy